Origin [compact disc, unabridged] : a novel - Brown, Dan, 1964- (Penguin Random House, 2017)
Robert Langdon, Harvard professor of symbology and religious iconology, is in Spain for the unveiling of billionaire Edmond Kirsch's major discovery. But when the controversial presentation erupts into chaos, Langdon sets out to unlock Kirsch's secret.